Dakwah Transformasional Berdasarkan Spiritualitas Kenabian: Analisis Wacana Dakwah Habib Umar bin Hafidz di Jakarta: Transformational Da'wah Based on Prophetic Spirituality: A Discourse Analysis of Habib Umar bin Hafidz's Preaching in Jakarta - Sugito; Sarbini Anim; Badrah Uyuni (Al-Ma‘ani: Journal of Islamic Studies, 2026)
Contemporary urban Muslim communities experience spiritual fragmentation, psychological pressure, and existential anxiety as consequences of modernization, digital acceleration, and urban lifestyles. This study aims to analyze the construction of discourse, dominant messages, and transformational values embedded in the preaching of Habib Umar bin Hafidz in Jakarta together with Majelis Rasulullah SAW. The research employs a qualitative approach using Content Analysis integrated with Critical Discourse Analysis (CDA). Primary data were obtained from recordings of the YouTube broadcast “Rihlah Jakarta 2025.” The data were analyzed through thematic coding, discourse interpretation, and ideological analysis to identify patterns of spiritual communication and the construction of religious meaning. The findings reveal that the dominant themes of the preaching include love for Prophet Muhammad, strengthening of tawhid, spiritual purification, prophetic morality, and Islamic brotherhood. The study further shows that Habib Umar employs a humanistic, persuasive, and non-confrontational preaching model characterized by emotional spirituality, compassionate narratives, and reflective religious discourse. This study proposes the concept of “transformational da’wah based on prophetic spirituality” as an alternative framework for understanding contemporary urban da’wah. The findings contribute to the study of Islamic communication by demonstrating that prophetic spirituality functions not only as theological discourse but also as emotional healing, identity construction, and social transformation within modern urban Muslim communities.